Pathways affect vegetation structure and composition in the Atlantic Forest in southeastern Brazil - Silva, Bruna Goncalves da; Devides Castello, Ana Carolina [UNESP]; Koch, Ingrid; Silva, Wesley Rodrigues (Soc Botanica Brasil, 2017)
Although impacts generated by gaps can affect vegetation, few studies have addressed these impacts in the Atlantic Forest. Our aim was to investigate the effects of pathways of varying widths on vegetation structure and composition, considering dispersal syndromes, diversity, life forms, successional categories and threatened and exotic species occurrence in the Atlantic Forest. We studied three pathways with widths of 2, 10 and 20 m, intersecting a protected area in southeastern Brazil. To assess edge effects, plots were established adjacent to paths (edge) and 35 m from the edge (neighborhood), and in a control area without pathways. Wider pathways (10 and 20 m) exhibited reduced tree height and diameter, high liana density, exotic species, and a high proportion of pioneer and anemochorous species. In conclusion, our results indicate that the vegetation structure of narrow pathways (2 m) is similar to the control area, and that wide linear gaps cause negative effects on vegetation and extend to a distance of at least 35 m into the forest interior. Considering that linear gaps generate permanent effects to vegetation and may affect other organisms, we suggest that these effects must be considered for successful management of protected areas, including planning and impact mitigation.
Keywords: Carlos Botelho State Park; conservation; linear gaps; plants; roads; trails